Sense of campus community and student satisfaction in public universities in Uganda - Samuel Lukenge; Wilson Mugizi; Mathias Mathias (International Journal of Educational Policy Research and Review, 2026)
Student satisfaction is widely recognised as an important indicator of quality in higher education because it reflects the extent to which universities meet students’ academic and social needs. This study examined the influence of sense of campus community on student satisfaction in public universities in Uganda. Specifically, it investigated the extent to which membership, influence, shared emotional connection, and integration and fulfilment of needs predict students' intrinsic and extrinsic satisfaction. Guided by the Psychological Sense of Community Theory, the study adopted a quantitative correlational research design. Data were collected from 393 undergraduate students, drawn from a population of 11,913 students in four public universities. The participants were predominantly final-year students from the Faculties of Science and Schools of Education. Data were collected using a structured self-administered questionnaire. Results indicated that both sense of campus community and student satisfaction were at moderate levels. Correlation analysis revealed that all dimensions of sense of campus community were positive and significantly associated with student satisfaction, with influence exhibiting the strongest relationship, followed by shared emotional connection, membership, and integration and fulfilment of needs. Regression analysis further showed that influence, shared emotional connection, and integration and fulfilment of needs significantly predicted student satisfaction, whereas membership was positive but not a significant predictor. The study concludes that strengthening students’ sense of campus community can contribute to greater satisfaction with their university experience. Universities should therefore create supportive environments that encourage student participation, meaningful social connections, a sense of belonging, and the fulfilment of students’ academic and social needs.